AKURASI PULSE OKSIMETRI UNTUK MENDETEKSI DILATASI VASKULAR INTRAPULMONER (DVIP) PADA PASIEN SIROSIS HATI - Sujana, I Ketut; Wibawa, I Dewa Nyoman; Santoso, Anwar (journal of internal medicine, 2008)
Hepatopulmonary syndrome (HPS) is a complication of liver cirrhotic in the lung. This clinicalsyndrome has three components; liver disease, intrapulmonary vascular dilatation (IPVD), and a defect inoxygenation. Transthoraxic echocardiography with contras enhancement (CE-TTE) is a gold standart methodbut still expensive and difficult to detect IPVD because it needs expertise. Therefore, a simple non-invasivemethod to detect IPVD would be desirable. In this study pulse oximetry was evaluated as predictor foridentification of IPVD in patient with liver cirrhotic.Objective of ythis study is to determine the diagnostic accuracy of pulse oxymetry in detection IPVDcompared with CE-TTE as a gold standart. The diagnostic test was perfomed with pulse oxyimetry in 49consecutive patient with liver cirrhotic of >17 years old without primary cardiopulmonary diseases. Oxygensaturation (SO2) was determined using a pulse oximeter in supine and upright position. The IVPD measured byCE-TTE as gold standard. Measurement of predictor and effect variables were singgle blinded which mean thedifferent examiner, each of them does not know the result of others. Sensitivity, specificity, positif predictivevalue, negative predictive value, accuracy, and likelihood ratio was calculated with computer programmed.Eight patients (16.3%) had IPVD and fourty (83.7%) without IPVD. The cut off SO2 95.5 % in supineposition can predict IPVD with sensitivity 97.6% (CI 95% 72.8;100.0), specificity 87.5% (CI95% 93.2;100.0),positif predictive value 87. 0% (CI95% 78.2;96.7) negative predictive value 100% (CI95% 72.8;100.0),accuracy 95% (CI95% 75.8;100.0), positif likelihood ratio 7.8, and negatif likelhood ratio 0.3. The cut off SO293.0 % in upright position can predict IPVD with sensitivity 100% (CI95% 94.2;100.0), specificity 87.5%(CI95% 78.2;96.7), positif predictive value 100% (CI95% 94.2;102.2), negative predictive value 97.6 %(CI95% 93.4;100.0), accuracy 97.5%(94.1;100.0), positif likelihood ratio 8, and negatif likelhood ratio 0. Thecut off slope oxygen saturation from supine to upright position ( SO2) 2.5% can predict IPVD with sensitivity100% (CI95% 97.2;100.1), specificity 95.1% (CI95% 89.1;100.0), positif predictive value 80% (CI95% 52.0;100.0), negative predictive value 100 %, accuracy 100% (97.1;100.0), positif likelihood ratio 20.4, andnegatif likelhood ratio 0. Pulse oxymetry is accurate predictor to detect of IPVD in liver cirrhotic patientwithout primary cardiopulmonary disease.